Effects of an intervention to prevent the bullying in first-grade secondary schools of Palermo, Italy: the BIAS study - Claudio Costantino; Alessandra Casuccio; Claudia Marotta; Stefania Enza Bono; Gianmarco Ventura; Walter Mazzucco; Francesco Vitale; Vincenzo Restivo; and the BIAS Study Working Group (BMC, 2019)
Abstract Background Bullying is one of the most common expressions of violence in the peer context during school years. This study investigates the prevalence of bullying and the short-term effects on students' bullying perceptions of a preventive intervention conducted among teachers of first-grade secondary schools in Palermo, Sicily (Italy). Methods Between the 2017/2018 and 2018/2019 school years, a pre-post intervention study was conducted among nine school institutions, sampled and categorized by neighbourhood socioeconomic index. A questionnaire investigating physical, verbal, and indirect bullying, the role of observers, prosociality, and resiliency in bullying was administered before and after intervention with formative cascade training of the teachers of the selected classes. Three different methods (sentinel questions, the five-question method, the 'score of seven' method) were used to detect the baseline level of bullying. Results A total of 402 students participated in the study (72.7% response rate). A decrease in the number of bullying episodes after the intervention was reported by the students in all types of bullying explored (physical, verbal, and indirect bullying, observers, resiliency, and prosociality), with all three methods. In particular, a statistically significant decrease in all the bullying areas investigated (except for resiliency) was reported for students attending schools of an intermediate socioeconomic level. Conclusions Even if many school-based interventions have been implemented to reduce school bullying throughout the world, this is one of the first conducted in Europe and it assesses the effectiveness among students of an anti-bullying intervention tailored for teachers. The encouraging results in reducing the number of bullying episodes together with the low cost in terms of human and economic resources could suggest an extension of this research on a regional/national scale.